Dpy19l1, a multi-transmembrane protein, regulates the radial migration of glutamatergic neurons in the developing cerebral cortex - Watanabe, Keisuke (Company of Biologists, 2011)
During corticogenesis, the regulation of neuronal migration is crucial for the functional organization of the neocortex. Glutamatergic neurons are major excitatory components of the mammalian neocortex. In order to elucidate the specific molecular mechanisms underlying their development, we used single-cell microarray analysis to screen for mouse genes that are highly expressed in developing glutamatergic neurons. We identified dpy-19-like 1 (Dpy19l1), a homolog of C. elegans dpy-19, which encodes a putative multi-transmembrane protein shown to regulate directed migration of Q neuroblasts in C. elegans. At embryonic stages Dpy19l1 is highly expressed in glutamatergic neurons in the mouse cerebral cortex, whereas in the subpallium, where GABAergic neurons are generated, expression was below detectable levels. Downregulation of Dpy19l1 mediated by shRNA resulted in defective radial migration of glutamatergic neurons in vivo, which was restored by the expression of shRNA-insensitive Dpy19l1. Many Dpy19l1-knockdown cells were aberrantly arrested in the intermediate zone and the deep layer and, additionally, some extended single long processes towards the pial surface. Furthermore, we observed defective radial migration of bipolar cells in Dpy19l1-knockdown brains. Despite these migration defects, these cells correctly expressed Cux1, which is a marker for upper layer neurons, suggesting that Dpy19l1 knockdown results in migration defects but does not affect cell type specification. These results indicate that Dpy19l1 is required for the proper radial migration of glutamatergic neurons, and suggest an evolutionarily conserved role for the Dpy19 family in neuronal migration.